Individual and combined toxicity of T‐2 toxin and deoxynivalenol on human C‐28/I2 and rat primary chondrocytes. Issue 2 (25th September 2018) - Lin, Xialu; Shao, Wanzhen; Yu, Fangfang; Xing, Ke; Liu, Huan; Zhang, Feng'e; Goldring, Mary B.; Lammi, Mikko J.; Guo, Xiong
Abstract: Deoxynivalenol (DON) and T‐2 toxin are prevalent mycotoxin contaminants in the food and feed stuffs worldwide, with non‐negligible co‐contamination and co‐exposure conditions. Meanwhile, they are considerable risk factors for Kashin‐Beck disease, a chronic endemic osteochondropathy. The aim of this study was to investigate the individual and combined cytotoxicity of DON and T‐2 toxin on proliferating human C‐28/I2 and newborn rat primary costal chondrocytes by MTT assay. Four molar concentration combination ratios of DON and T‐2 toxin were used, 1:1 for R1 mixture, 10:1 for R10, 100:1 for R100 and 1000:1 for R1000. The toxicological interactions were quantified by the MixLow method. DON, T‐2 toxin, and their mixtures all showed a clear dose‐dependent toxicity for chondrocytes. The cytotoxicity of T‐2 toxin was 285‐fold higher than DON was in human chondrocytes, and 22‐fold higher in the rat chondrocytes. The combination of DON and T‐2 toxin was significantly synergistic at middle and high level concentrations of R10 mixtures in rat chondrocytes, but significantly antagonistic at the low concentrations of R100 mixtures in both cells and at the middle concentrations of R1000 mixtures in rat chondrocytes. These results indicated that the combined toxicity was influenced by the cell sensitivity for toxins, the difference between the combination ratio and equitoxic ratio, the concentrations and other factors. Abstract : Deoxynivalenol (DON) and T‐2 toxin are prevalent mycotoxin contaminants and a risk factor for Kashin‐Beck disease. The individual and combined cytotoxicity of DON and T‐2 toxin were investigated on human C‐28/I2 and rat primary chondrocytes. The cytotoxicities of T‐2 toxin and DON are varied in different chondrocytes. Synergistic, antagonistic or additive toxicological interactions were observed in the binary mixture at different combination ratios. It suggested that the combined toxicity was influenced by cell sensitivity, combination ratios and concentrations.